2016
DOI: 10.1039/c6cc00349d
|View full text |Cite
|
Sign up to set email alerts
|

endo-Functionalized molecular tubes: selective encapsulation of neutral molecules in non-polar media

Abstract: Four endo-functionalized molecular tubes with urea/thiourea groups in the deep cavities have been synthesized, and their binding ability to neutral molecules studied. Very high binding affinity and selectivity have been achieved, which are rationalized by invoking the shape and electrostatic complementarity and dipole alignment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 31 publications
2
25
0
1
Order By: Relevance
“…Only guest 8 gives rise to a binding constant of 6.9 L∙mol –1 ; while the other five guests do not show obvious binding at all. This is in great contrast to the urea/thioureal naphthotubes, which can effectively bind these guests . Most surprisingly, dibenzo‐1,4‐dioxin 9 , which is structurally very similar to phenazine and contains two oxygen instead of nitrogen atoms, is not a guest to TM1 .…”
Section: Resultsmentioning
confidence: 88%
“…Only guest 8 gives rise to a binding constant of 6.9 L∙mol –1 ; while the other five guests do not show obvious binding at all. This is in great contrast to the urea/thioureal naphthotubes, which can effectively bind these guests . Most surprisingly, dibenzo‐1,4‐dioxin 9 , which is structurally very similar to phenazine and contains two oxygen instead of nitrogen atoms, is not a guest to TM1 .…”
Section: Resultsmentioning
confidence: 88%
“…[3][4][5] On this basis, we reported molecular tubes with endo-functionalized urea and thiourea groups and carefully studied their molecular recognition behaviour to neutral molecules. [2,6] In this presentation our continued efforts to encapsulate neutral guests inside these endo-functionalized molecular tubes and the obtained crystallographic results are demonstrated.…”
Section: S386mentioning
confidence: 90%
“…For example, endo-functionalized receptors reject the guests with appropriate shape but inappropriate electrostatic surface, and show a high binding affinity to the guests with both shape and electrostatic complementarity. [1,2] The title compounds of this presentation, endo-functionalized molecular tubes, have rarely been reported in the literature. [2] Recently, it has been demonstrated that naphthalene and the bisnaphthalene cleft are very good scaffolds for constructing molecular receptors.…”
Section: S386mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Recently Jiang and coworkers reported synthesis of the rigid, electron rich and nonchiral bisnaphthalene cleft based molecular receptor referred as endofunctionalized molecular tubes with the converging urea/ thiourean functionalties. [18][19][20][21][22] The configurational isomers of such molecular scaffold are displayed in Scheme 1. It has been realized that the molecular attributes such as cooperativity between the deep cavity of the host and bridging urea group, nonzero dipole moment etc.…”
Section: Introductionmentioning
confidence: 99%